Adat Bertemu Syariat: Studi Islamisasi Tradisi Wiwitan di Desa Semampir, Banjarnegara - Dwi Kuswianto; Cinanthya Yuwono (SETYAKI : Jurnal Studi Keagamaan Islam, 2025)
This study aims to examine the process of Islamization of the Wiwitan tradition in Semampir Village, Banjarnegara, as a dynamic encounter between local customs and Islamic Sharia values. The Wiwitan tradition, which is rich in symbolic meanings and ancestral practices, has undergone transformation in line with the community’s growing Islamic awareness. Employing a qualitative-descriptive approach and ethnographic methods, data were collected through participatory observation from January to February 2025, in-depth interviews with religious leaders, cultural figures, and youth, as well as document analysis. The findings reveal that the process of Islamization occurs gradually and dialogically, rather than through direct rejection of local customs. The reinterpretation of meanings, adaptation of ritual symbols, and active involvement of local figures have turned the tradition into an effective medium for cultural da'wah. Islam does not emerge as a hegemonic force but instead blends harmoniously with local cultural structures. The integration of custom and Sharia creates a new space for religiosity that is inclusive and contextual. These findings highlight the importance of culturally based approaches in fostering a moderate Islamic society rooted in local wisdom and open to change